A Champion of Host Defense: A Generic Large-Scale Cause for Platelet Dysfunction and Depletion in Infection - Page, Martin J.; Pretorius, Etheresia (Seminars in Thrombosis and Hemostasis, 2020)
Thrombocytopenia is commonly associated with sepsis and infections, which in turn are characterized by a profound immune reaction to the invading pathogen. Platelets are one of the cellular entities that exert considerable immune, antibacterial, and antiviral actions, and are therefore active participants in the host response. Platelets are sensitive to surrounding inflammatory stimuli and contribute to the immune response by multiple mechanisms, including endowing the endothelium with a proinflammatory phenotype, enhancing and amplifying leukocyte recruitment and inflammation, promoting the effector functions of immune cells, and ensuring an optimal adaptive immune response. During infection, pathogens and their products influence the platelet response and can even be toxic. However, platelets are able to sense and engage bacteria and viruses to assist in their removal and destruction. Platelets greatly contribute to host defense by multiple mechanisms, including forming immune complexes and aggregates, shedding their granular content, and internalizing pathogens and subsequently being marked for removal. These processes, and the nature of platelet function in general, cause the platelet to be irreversibly consumed in the execution of its duty. An exaggerated systemic inflammatory response to infection can drive platelet dysfunction, where platelets are inappropriately activated and face immunological destruction. While thrombocytopenia may arise by condition-specific mechanisms that cause an imbalance between platelet production and removal, this review evaluates a generic large-scale mechanism for platelet depletion as a repercussion of its involvement at the nexus of responses to infection.
Keywords: platelets; virus; bacteria; thrombocytopenia; immune response